Cuidados de enfermagem para avaliação, prevenção e tratamento da xerose cutânea em pessoas idosas - Cruz, Ronny Anderson de Oliveira (2019)
Introduction: When considering the common alterations in the aging process, cutaneous xerosis characterized by dryness presents a high frequency and can generate complications for the elderly. Objective: Analyse nursing care for evaluation, prevention and treatment of cutaneous xerosis in the elderly. Method: This is a descriptive study with a quantitative approach, carried out with 101 care nurses from four hospitals in the city of João Pessoa-PB, between July and September 2018. The inclusion criteria were: to work in the units as care nurses, be in the service for at least six months and use the nursing process in care. Nurses who worked only in administrative functions were excluded from the survey, or were separated by leave or leave during the collection period. The operational stages were: 1 - theoretical-reflective study on the contributions of Nursing Theory Wanda Aguiar Horta; 2 - integrative review of the literature; 3 - construction and validation of instrument content; 4 - application of the instrument; and 5 - instrument construct validation. Descriptive statistical analyzes of distribution and frequency were performed to analyze the data. A chi-square test was also performed for categorical variables and exploratory factor analysis for construct validation. It was approved by the Ethics and Research Committee of the Health Sciences Center of the Federal University of Paraíba under the number of CAAE: 89318318.3.0000.5188. Results: There was emphasis on the importance of considering the age group and observing the existence of lesions. Of the participating professionals, 64.4% reported not having any course related to the prevention or treatment of skin lesions. From the factorial analysis, three construct factors were defined for the instrument with total explanatory variance of 47.77%, Bartlett's sphericity test with p <0.001 and the general Cronbach's alpha of 0.811. Conclusion: The study demonstrated the importance and necessity of permanent education to improve the quality of care and the instrument was valid and reliable, contributing to the practice of nurses as an integral part of the process of caring for the elderly.